Dynamic Bradley–Terry modelling of sports tournaments. Issue 1 (31st May 2012) - Cattelan, Manuela; Varin, Cristiano; Firth, David
<x xml:space="preserve">Abstract</x> Summary. In the course of national sports tournaments, usually lasting several months, it is expected that the abilities of teams taking part in the tournament will change over time. A dynamic extension of the Bradley–Terry model for paired comparison data is introduced to model the outcomes of sporting contests, allowing for time varying abilities. It is assumed that teams' home and away abilities depend on past results through exponentially weighted moving average processes. The model proposed is applied to sports data with and without tied contests, namely the 2009–2010 regular season of the National Basketball Association tournament and the 2008–2009 Italian Serie A football season.